INVENTARISASI JAMUR MAKROSKOPIS FILUM ASCOMYCOTA DI KAWASAN UNIVERSITAS TANJUNGPURA PONTIANAK KALIMANTAN BARAT - Kristin, Repita; Rahmawati, Rahmawati; Mukarlina, Mukarlina (Universitas Tanjungpura, 2020)
Ascomycota is a microscopic fungi and a fraction of macroscopic, unicellular and multicellular fungi. The research of Ascomycota phylum macroscopic fungi inventory research aims to determine the type macroscopic fungi of Ascomycota phylum members in Tanjungpura University Area, Pontianak, West Borneo. The sample was taken by using Cruise Method and identified by matching morphological characteristics of the specimens with the identification book.Â AscomycotaÂ identification of macroscopic fungi samples of Ascomycota phylum based on morphological characteristics with the identification books. The results study found have 3 macroscopic fungi species consisting of 2 classes, 2 orders, 2 families, and 2 genera. In addition, Ascomycota found in Tanjungpura University Area, Pontianak, West Borneo, grow mostly on the substrate originated from dead trees.